Intersecting journeys in creating learning communities in executive education. Issue 3 (September 2013) - Beechler, Schon; Ciporen, Rachel; Yorks, Lyle
This article explores the findings from an action research project which tracked the evolution of The Executive Program (EP) (a pseudonym), a four-week open enrollment senior executive program at a major university in the United States. The decade-long journey grew from a program redesign initiative to a process of ongoing change through insider action research. Through the process the faculty director and collaborating faculty unexpectedly experienced an epistemological shift. The EP was transformed from a traditional 'teacher as expert' model with a focus on cognitive learning to a holistic learning community that emphasized broader participant involvement and a wider range of learning approaches. This article is the product of the authors' collaborative meaning-making through the lens of developmental action inquiry and adult learning theory.